Dielectric ceramic, energy storage-fluorescent dielectric capacitor with transparent shell based on dielectric ceramic and method

By using Dy3+ doped Bi0.5Na0.5TiO3 and BaTiO3 or SrTiO3 binary solid solution as dielectric ceramic materials, and optimizing the material formula and preparation process, the problems of low energy storage density and weak fluorescence intensity of energy storage-fluorescent dielectric capacitors are solved, and a dielectric capacitor with high energy storage density and strong fluorescence performance are achieved, which is suitable for non-contact non-destructive testing.

CN119528566APending Publication Date: 2025-02-28XIAN UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411737890.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing energy storage-fluorescent dielectric capacitors have low energy storage density and weak fluorescence intensity, and the high transmittance electrodes and packaging shells of traditional dielectric capacitors are difficult to meet the needs of commercial use.

Method used

Dy3+ doped Bi0.5Na0.5TiO3 and BaTiO3 or SrTiO3 are used as dielectric ceramic materials, and their dielectric, polarization, temperature stability and fluorescence properties are improved by optimizing the material formulation and preparation process of dielectric ceramics, transparent electrodes and transparent shells.

Benefits of technology

The dense structure of dielectric ceramics is achieved, with small grain size and uniform element distribution, thus showing excellent characteristics of large dielectric constant, good energy storage performance, high fluorescence intensity and emitted light close to white light, and is suitable for non-contact non-destructive testing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528566A_ABST
    Figure CN119528566A_ABST
Patent Text Reader

Abstract

The invention discloses a dielectric ceramic, an energy storage-fluorescent dielectric capacitor with a transparent shell based on the dielectric ceramic and a method, and belongs to the technical field of lead-free dielectric ceramic capacitors. The dielectric ceramic disclosed by the invention has the characteristics of compact structure, small grain size and uniform element distribution, so that the dielectric ceramic has the excellent characteristics of large dielectric constant, good energy storage performance, high fluorescence intensity and capability of emitting light close to white light. The energy storage-fluorescent dielectric capacitor with the transparent shell disclosed by the invention has the characteristics of high light transmittance, high use temperature and sensitive fluorescent detection, is suitable for the field of non-contact nondestructive detection of dielectric capacitors, and has a relatively high application value in the aspects of structural phase change monitoring, service failure and the like of the dielectric capacitors.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lead-free dielectric ceramic capacitors, and in particular relates to a dielectric ceramic and an energy storage-fluorescent dielectric capacitor with a transparent shell based thereon and a method. Background Art

[0002] With the rapid development of information technology, people's demand for miniaturized, lightweight and integrated electronic devices is increasing. Dielectric capacitors have the characteristics of high power density, fast charging and discharging speed and good stability, and are very suitable for pulse power systems. However, dielectric capacitors often face changes in high temperature, extreme cold and other environments during service, which may cause dielectric capacitors to experience drastic performance fluctuations. Therefore, fast and efficient performance monitoring is of great significance for evaluating the life of dielectric capacitors and preventing product failure. However, for packaged dielectric capacitor devices, conventional detection methods such as X-ray diffraction, Raman, dielectric temperature spectrum, etc. are often destructive, so it is necessary to develop a new type of efficient non-destructive and non-contact detection method. In recent years, multifunctional dielectric capacitors with both fluorescence and energy storage characteristics have gradually become one of the main research objects. Researchers usually dope rare earth elements into the lattice of ferroelectric ceramics. The 4f energy level of rare earth ions couples with the crystal field, making the optical properties of rare earth ions very sensitive to the local symmetry of the chemical and lattice environment around the doped rare earth sites. By detecting changes in optical properties such as luminescence intensity and luminescence color, they can ultimately achieve non-destructive and non-contact detection of crystal structure and dielectric properties, and achieve the purpose of dynamically evaluating the service life of the device. Therefore, the development of high-performance fluorescent-energy storage dielectric capacitors has broad commercial prospects.

[0003] Professor Wei Xianhua's research group at Southwest University of Science and Technology reported a Eu 3+ Doped SrTiO3-based energy storage-fluorescent ferroelectric ceramics (Journal of Alloys and Compounds 901 (2022) 163556), which have good dielectric and energy storage properties and exhibit red light emission fluorescence characteristics. The research group of Professor Jianhua Hao of the Hong Kong Polytechnic University reported Yb / Er co-doped barium titanate epitaxial films, and achieved electroluminescent enhancement and dynamic modulation of upconversion photoluminescence by growing SRO and ITO electrodes on the upper and lower plates (Angew. Chem. 2011, 123, 7008-7012). However, the current energy storage-fluorescent dielectric capacitors still have the characteristics of low energy storage density and weak fluorescence intensity. More importantly, compared with the opaque silver paste electrodes and polymer shells of traditional sheet ceramic capacitors, energy storage-fluorescent dielectric capacitors need to achieve highly transparent electrodes and packaging shells, but the high-transmittance electrodes and packaging shells of current dielectric capacitors are still difficult to meet the needs of commercial use, and it is urgent to further optimize the material composition and packaging process of electrodes and shells. Summary of the invention

[0004] The object of the present invention is to provide a dielectric ceramic and an energy storage-fluorescence dielectric capacitor with a transparent shell based thereon and a method, so as to solve the technical problems of low energy storage density and weak fluorescence intensity of the current energy storage-fluorescence dielectric capacitor.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: The invention discloses a dielectric ceramic, the chemical formula of which is nBi x Dy i Na 0.5 TiO3-(1-n)BaTiO3 or nBi x Dy i Na 0.5 TiO3-(1-n)SrTiO3; wherein: wherein: 0.75≤n≤0.94; 0.45≤x≤0.475; 0.025≤i≤0.035.

[0006] Furthermore, the chemical formula of the dielectric ceramic is 0.94Bi 0.475 Dy 0.025 Na 0.5 TiO3-0.06BaTiO3, 0.75Bi (703 / 1500) Dy (47 / 1500) Na 0.5 TiO3-0.25BaTiO3, 0.94Bi 0.475 Dy 0.025 Na 0.5 TiO3-0.06SrTiO3 or 0.75Bi (703 / 1500) Dy (47 / 1500) Na 0.5 TiO3-0.25SrTiO3.

[0007] The present invention also discloses a method for preparing the above dielectric ceramic, comprising the following steps: Weigh Bi2O3, Ba2CO3, Na2CO3, Dy2O3, SrCO3 and TiO2 as raw materials according to the stoichiometric ratio of claim 1 or 2; The raw materials are ball-milled once, and the obtained slurry is dried and pre-sintered in sequence to obtain a ceramic powder precursor; The ceramic powder precursor is subjected to secondary ball milling, tableting, cold isostatic pressing and sintering in sequence to obtain dielectric ceramics.

[0008] Furthermore, the purity of Bi2O3, Ba2CO3, Na2CO3, Dy2O3, SrCO3 and TiO2 is not less than 99.5%; The rotation speed of the first ball milling and the second ball milling is 600-650 r / min, the ball milling time is 20-32 h, and the ball milling medium is one of anhydrous ethanol or distilled water; The drying time is 12-24 h; the pre-burning temperature is 855-875°C and the time is 3-5 h.

[0009] Furthermore, the tableting pressure is 1.5-4 MPa, and the holding time is 1-5 min; The pressure during the cold isostatic pressing process is 100-300 MPa, and the holding time is 1-5 min.

[0010] Furthermore, the sintering treatment is carried out at a temperature of 1140-1160°C and for a time of 2-4 hours.

[0011] The present invention also discloses an energy storage-fluorescent dielectric capacitor with a transparent shell, the components of which include the above-mentioned dielectric ceramic, a transparent conductive electrode, a pin and a transparent shell; The transparent conductive electrode is arranged on the surface of the dielectric ceramic; the pins are welded on both sides of the dielectric ceramic; and the transparent shell is encapsulated outside the dielectric ceramic, the transparent conductive electrode and the pins.

[0012] The present invention also discloses a method for preparing the energy storage-fluorescent dielectric capacitor having a transparent shell, comprising the following steps: A transparent conductive electrode is sputtered on the surface of the dielectric ceramic, and then a lead is welded on both sides of the dielectric ceramic to obtain a component; A transparent shell is encapsulated on the outside of the component to obtain an energy storage-fluorescent dielectric capacitor with a transparent shell.

[0013] Furthermore, the specific process of sputtering the transparent conductive electrode is: First, the vacuum degree in the deposition chamber was pumped down to 5×10 -5 Pa; then introduce a mixed gas of argon and oxygen in a volume ratio of 99.5:0.5 into the deposition chamber to keep the pressure in the deposition chamber stable at 0.5-2Pa; Then, a transparent conductive electrode with a thickness of 20-40 nm was prepared according to the process parameters of DC sputtering power of 90-100 W, sample stage deposition temperature of 20-30 °C, and sputtering time of 30-60 min. Finally, after the above sputtering is completed, a mixed gas of argon and oxygen with a volume ratio of 99.5:0.5 is introduced to keep the pressure in the chamber stable at 1×10 4 - 3×10 4Pa, and raising the temperature of the sample stage to 500-600 °C and keeping the temperature for 1-3 hours to complete the annealing treatment of the electrode, thereby obtaining the transparent conductive electrode; The transparent conductive electrode is any one of ITO, AZO and FTO.

[0014] Furthermore, the pin welding temperature is 260-300°C; the transparent shell is a polymer transparent shell; the packaging temperature of the polymer transparent shell is 200-250°C, and the curing time is 5-10 min; The pins are tin-plated iron-aluminum alloy pins; the polymer material is one or two of PMMA, PC and epoxy resin E51.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a dielectric ceramic. In terms of material composition design, due to the use of Dy 3+ Bi doped at the morphotropic phase boundary (MPB) 0.5 Na 0.5 Binary solid solution of TiO3 and BaTiO3 or SrTiO3, the phase transition energy barrier of this component is low, the dielectric constant is large, and the effect of adjusting its dielectric, polarization, and temperature stability by means of ion doping and process control is very significant, and it can achieve excellent ferroelectric and dielectric properties. 3+ Doping can not only introduce lattice distortion, but also introduce white light emitting centers, thus 0.5 Na 0.5 The binary solid solution of TiO3 and BaTiO3 or SrTiO3 realizes local structural distortion. The changed local stress field and local electric field will significantly affect the Dy 3+ The inversion symmetry and fluorescence quenching characteristics of the luminescence center change the luminescence intensity and color temperature characteristics. Therefore, the obtained dielectric ceramic has a dense structure, small grain size, and uniform element distribution, thus showing excellent characteristics of large dielectric constant, good energy storage performance, high fluorescence intensity, and emission light close to white light.

[0016] The present invention also discloses a method for preparing the above-mentioned dielectric ceramics, which adopts lead-free and environmentally friendly raw materials and is processed through preparation processes such as high-speed ball milling, cold isostatic pressing and high-temperature sintering. The obtained dielectric ceramics have the characteristics of dense structure, small grain size and uniform element distribution, thereby showing excellent characteristics of large dielectric constant, good energy storage performance, high fluorescence intensity and emission light close to white light. The method is environmentally friendly, simple to operate and has broad application prospects.

[0017] The present invention also discloses an energy storage-fluorescence dielectric capacitor with a transparent shell obtained by using the above-mentioned dielectric ceramic. Since the dielectric ceramic adopts the preparation process of high-energy ball milling and double ball milling, it is ensured that the powder raw materials are mixed more evenly and the particles are ball milled finer. In addition, the process of powder screening, cold isostatic pressing and double sintering also makes the ceramic reaction more sufficient, ensuring the dielectric ceramic phase formation, porcelain formation and uniform diffusion in high-temperature reaction, so that the sintered ceramic has the advantages of dense flatness and few pores. The energy storage-fluorescence dielectric capacitor prepared by using the dielectric ceramic has the advantages of uniform and small ceramic grain size distribution, few defects such as holes and cracks, and less incident light scattering. The capacitor adopts a transparent shell, has the characteristics of high light transmittance, high operating temperature, and sensitive fluorescence detection, and is suitable for the field of non-contact non-destructive testing of dielectric capacitors, and has great application value in the aspects of structural phase change monitoring and service failure of dielectric capacitors.

[0018] The present invention also discloses a method for preparing the above-mentioned energy storage-fluorescent dielectric capacitor with a transparent shell, and utilizes magnetron sputtering to prepare a transparent conductive electrode. Compared with laser pulse technology, a small magnetron sputtering apparatus, screen printing and other processes, the prepared electrode has the characteristics of high light transmittance, density and flatness, and high conductivity, and has good bonding with the ceramic substrate and is not easy to fall off. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 A schematic diagram of the three-dimensional structure of an energy storage-fluorescent dielectric capacitor with a transparent shell prepared by the present invention; Figure 2 A schematic diagram of the two-dimensional structure of an energy storage-fluorescent dielectric capacitor with a transparent shell prepared by the present invention; Figure 3 X-ray diffraction spectra of dielectric ceramics prepared in Examples 1 to 4 of the present invention; Wherein: a, XRD spectrum in the range of 20°-80°; b, XRD spectrum peak magnification in the range of 38°-42°; Figure 4 The scanning electron microscope image of the dielectric ceramic prepared by the present invention and the corresponding grain size distribution statistical graph; Wherein: a, cross-sectional scan of the BNDT-0.25ST ceramic in Example 4; b, cross-sectional scan of the BNDT-0.25BT ceramic in Example 2; c, cross-sectional scan of the BNDT-0.06ST component ceramic in Example 3; d-cross-sectional scan of the BNDT-0.06BT ceramic in Example 1; Figure 5 The excitation spectra of the dielectric ceramics prepared in Examples 1 to 4 of the present invention are shown; Among them: a-ceramic excitation spectrum obtained under 483 nm monitoring; b-ceramic excitation spectrum obtained under 576 nm monitoring; Figure 6 The emission spectra of the dielectric ceramics prepared in Examples 1 to 4 of the present invention; Among them: a-ceramic emission spectrum obtained under 389 nm excitation; b-ceramic emission spectrum obtained under 427 nm excitation. DETAILED DESCRIPTION

[0020] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0021] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0022] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0023] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0024] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0025] The present invention provides a dielectric ceramic having a chemical composition of 0.94Bi 0.475 Dy 0.025 Na 0.5 TiO3-0.06BaTiO3, 0.75Bi (703 / 1500) Dy (47 / 1500) Na 0.5 TiO3-0.25BaTiO3, 0.94Bi0.475 Dy 0.025 Na 0.5 TiO3-0.06SrTiO3, 0.75Bi (703 / 1500) Dy (47 / 1500) Na 0.5 Any one of TiO3-0.25SrTiO3.

[0026] The present invention also provides a method for preparing the above dielectric ceramic, which is specifically implemented according to the following steps: Step 1: According to the chemical composition of dielectric ceramic 0.94Bi 0.475 Dy 0.025 Na 0.5 TiO3-0.06BaTiO3, 0.75Bi (703 / 1500) Dy (47 / 1500) Na 0.5 TiO3-0.25BaTiO3, 0.94Bi 0.475 Dy 0.025 Na 0.5 TiO3-0.06SrTiO3, 0.75Bi (703 / 1500) Dy (47 / 1500) Na 0.5 Any component of TiO3-0.25SrTiO3, weigh the raw materials Bi2O3, Ba2CO3, Na2CO3, Dy2O3, SrCO3 and TiO2 respectively; Step 2, placing the raw materials weighed in step 1 in a planetary ball mill to grind them evenly and then drying the slurry and pre-calcining them to obtain a ceramic powder precursor; Step 3: subject the ceramic powder precursor obtained in step 2 to secondary ball milling, tableting and cold isostatic pressing in sequence, and place the obtained cylindrical ceramic green body in a muffle furnace for sintering.

[0027] Preferably, the purity of Bi2O3, Ba2CO3, Na2CO3, Dy2O3, SrCO3 and TiO2 selected in step 1 is not less than 99.5%.

[0028] Preferably, the mixture after the first ball milling is placed in a glass dish for drying for 12 h, and during pre-firing, is placed in a muffle furnace for sintering at 855° C. for 4 h.

[0029] Preferably, the primary ball milling and the secondary ball milling are performed by planetary ball milling, the rotation speed is 600 r / min, the ball milling time is 24 h, and the medium used is one of anhydrous ethanol or distilled water.

[0030] Preferably, the tableting pressure is 1.5 MPa and the holding time is 1 min.

[0031] Preferably, the pressure during the cold isostatic pressing process is 300 MPa and the holding time is 1 min.

[0032] Preferably, the secondary sintering is performed in a muffle furnace at 1145° C. for 2 h.

[0033] The present invention also provides an energy storage-fluorescent dielectric capacitor with a transparent shell prepared by using the above dielectric ceramic, and the preparation process comprises the following steps: Sputtering a transparent conductive electrode on the dielectric ceramic, and then welding a tin-plated iron-aluminum alloy pin on both sides of the dielectric ceramic; Then seal it with a transparent shell.

[0034] Preferably, the transparent conductive electrode on the dielectric ceramic is any one of ITO (indium tin oxide), AZO (aluminum-doped zinc oxide), and FTO (fluorine-doped tin oxide); the material of the outermost transparent packaging shell is one of PMMA (polymethyl methacrylate), PC (polycarbonate), and epoxy resin E51 (Phoenix brand) or a combination of two.

[0035] Preferably, the specific process of preparing the transparent conductive electrode by magnetron sputtering is: First, the vacuum degree in the deposition chamber was pumped down to 5×10 -5 Pa; then introduce a mixed gas of argon and oxygen in a volume ratio of 99.5:0.5 into the deposition chamber to keep the pressure in the deposition chamber stable at 0.5-2Pa; Then, a transparent conductive electrode with a thickness of 20-40 nm was prepared according to the process parameters of DC sputtering power of 90-100 W, sample stage deposition temperature of 20-30 °C, and sputtering time of 30-60 min. Finally, after the above sputtering is completed, a mixed gas of argon and oxygen with a volume ratio of 99.5:0.5 is introduced to keep the pressure in the chamber stable at 1×10 4 - 3×10 4 Pa, and the sample stage is heated to 500-600°C and kept warm for 1-3 hours to complete the annealing treatment of the electrode, thereby obtaining the transparent conductive electrode.

[0036] Preferably, the soldering temperature of the tin-plated iron-aluminum alloy pin is 260°C.

[0037] Preferably, the packaging temperature of the polymer transparent shell is 200-250° C., and the curing time is 5-10 min.

[0038] The transparent packaged shell dielectric capacitor of the present invention has both energy storage and fluorescence properties, and has the characteristics of large energy storage density, excellent fluorescence performance, and high light transmittance. By optimizing the material formula of dielectric ceramics, transparent electrodes, and transparent shells and the corresponding preparation process, it is beneficial to obtain energy storage-fluorescence multifunctional properties. The packaged electrodes and shells with high light transmittance help to achieve non-contact non-destructive fluorescence detection, providing a solution for rapid and efficient detection and analysis of dielectric capacitors, and has broad commercial application prospects in component failure analysis, service monitoring, structural characterization, etc.

[0039] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0040] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0041] Example 1 A method for preparing a dielectric ceramic comprises the following steps: Step 1: According to 0.94Bi 0.475 Dy 0.025 Na 0.5 The chemical formula stoichiometric ratio of TiO3-0.06BaTiO3 is as follows: Bi2O3, Ba2CO3, Na2CO3, Dy2O3, SrCO3 and TiO2 with a purity higher than 99.5% from Aladdin Company are weighed as raw materials; Step 2: The weighed raw materials are placed in a nylon ball mill filled with zirconium oxide balls, anhydrous ethanol is added as a ball milling medium, and ball milling is performed once. The speed of the ball milling is 600 r / min, and the ball milling time is 24 h; the obtained slurry is placed in a petri dish and dried at 100 ° C for 12 h; the dried powder is placed in an alumina crucible and pre-sintered at 855 ° C for 4 h to obtain a ceramic powder precursor; Step 3: The ceramic powder precursor is crushed and ball-milled twice using anhydrous ethanol as a medium. The ball milling speed is 600 r / min and the ball milling time is 24 h. After the ball milling is completed, the slurry is treated according to the same drying process as step 2, and then the dried powder is fully ground and passed through a 150-mesh sieve to obtain a uniform and fine powder; 0.25 g of the above powder is weighed and loaded into a cylindrical mold with a diameter of 10 mm, and then an electric tablet press is used to obtain a ceramic disc at a pressure of 1.5 MPa and a holding time of 1 min, and then a cold isostatic press is used to obtain a dense, crack-free unsintered sheet ceramic at a pressure of 300 MPa and a holding time of 1 min; Step 4: Place the above ceramic sheet in a muffle furnace for sintering treatment. The treatment process is to keep warm at 1145 °C for 2 hours. The sintering atmosphere is air. The heating rate of the muffle furnace during sintering is 5 °C / min. The cooling method is natural cooling with the furnace. The sintered dielectric ceramic sheet is polished with 1000 mesh and 2000 mesh sandpaper until it is smooth to obtain dielectric ceramics.

[0042] Example 2 A method for preparing a dielectric ceramic comprises the following steps: Step 1: According to 0.75Bi (703 / 1500) Dy (47 / 1500) Na 0.5 Stoichiometric ratio of TiO3-0.25BaTiO3 Bi2O3, Ba2CO3, Na2CO3, Dy2O3, SrCO3 and TiO2 with purity higher than 99.5% from Aladdin Company were weighed as raw materials; Step 2: The weighed raw materials are placed in a nylon ball mill filled with zirconium oxide balls, anhydrous ethanol is added as a ball milling medium, and ball milling is performed once. The speed of the ball milling is 600 r / min, and the ball milling time is 24 h; the obtained slurry is placed in a petri dish and dried at 100 ° C for 12 h; the dried powder is placed in an alumina crucible and pre-sintered at 855 ° C for 4 h to obtain a ceramic powder precursor; Step 3: The ceramic powder precursor is crushed and ball-milled twice using anhydrous ethanol as a medium. The ball milling speed is 600 r / min and the ball milling time is 24 h. After the ball milling is completed, the slurry is treated according to the same drying process as step 2, and then the dried powder is fully ground and passed through a 150-mesh sieve to obtain a uniform and fine powder; 0.25 g of the above powder is weighed and loaded into a cylindrical mold with a diameter of 10 mm, and then an electric tablet press is used to obtain a ceramic disc at a pressure of 1.5 MPa and a holding time of 1 min, and then a cold isostatic press is used to obtain a dense, crack-free unsintered sheet ceramic at a pressure of 300 MPa and a holding time of 1 min; Step 4: Place the above ceramic sheet in a muffle furnace for sintering treatment. The treatment process is to keep warm at 1145 °C for 2 hours. The sintering atmosphere is air. The heating rate of the muffle furnace during sintering is 5 °C / min. The cooling method is natural cooling with the furnace. The sintered dielectric ceramic sheet is polished with 1000 mesh and 2000 mesh sandpaper until it is smooth to obtain dielectric ceramics.

[0043] Example 3 A method for preparing a dielectric ceramic comprises the following steps: Step 1: According to 0.94Bi 0.475 Dy 0.025 Na 0.5 Stoichiometric ratio of TiO3-0.06SrTiO3 Bi2O3, Ba2CO3, Na2CO3, Dy2O3, SrCO3 and TiO2 with purity higher than 99.5% from Aladdin Company were weighed as raw materials; Step 2: The weighed raw materials are placed in a nylon ball mill filled with zirconium oxide balls, anhydrous ethanol is added as a ball milling medium, and ball milling is performed once. The speed of the ball milling is 600 r / min, and the ball milling time is 24 h; the obtained slurry is placed in a petri dish and dried at 100 ° C for 12 h; the dried powder is placed in an alumina crucible and pre-sintered at 855 ° C for 4 h to obtain a ceramic powder precursor; Step 3: The ceramic powder precursor is crushed and ball-milled twice using anhydrous ethanol as a medium. The ball milling speed is 600 r / min and the ball milling time is 24 h. After the ball milling is completed, the slurry is treated according to the same drying process as step 2, and then the dried powder is fully ground and passed through a 150-mesh sieve to obtain a uniform and fine powder; 0.25 g of the above powder is weighed and loaded into a cylindrical mold with a diameter of 10 mm, and then an electric tablet press is used to obtain a ceramic disc at a pressure of 1.5 MPa and a holding time of 1 min, and then a cold isostatic press is used to obtain a dense, crack-free unsintered sheet ceramic at a pressure of 300 MPa and a holding time of 1 min; Step 4: Place the above ceramic sheet in a muffle furnace for sintering treatment. The treatment process is to keep warm at 1145 °C for 2 hours. The sintering atmosphere is air. The heating rate of the muffle furnace during sintering is 5 °C / min. The cooling method is natural cooling with the furnace. The sintered dielectric ceramic sheet is polished with 1000 mesh and 2000 mesh sandpaper until it is smooth to obtain dielectric ceramics.

[0044] Example 4 A method for preparing a dielectric ceramic comprises the following steps: Step 1: According to 0.75Bi (703 / 1500) Dy (47 / 1500) Na 0.5Stoichiometric ratio of TiO3-0.25SrTiO3 Bi2O3, Ba2CO3, Na2CO3, Dy2O3, SrCO3 and TiO2 with purity higher than 99.5% from Aladdin Company were weighed as raw materials; Step 2: The weighed raw materials are placed in a nylon ball mill filled with zirconium oxide balls, anhydrous ethanol is added as a ball milling medium, and ball milling is performed once. The speed of the ball milling is 600 r / min, and the ball milling time is 24 h; the obtained slurry is placed in a petri dish and dried at 100 ° C for 12 h; the dried powder is placed in an alumina crucible and pre-sintered at 855 ° C for 4 h to obtain a ceramic powder precursor; Step 3: The ceramic powder precursor is crushed and ball-milled twice using anhydrous ethanol as a medium. The ball milling speed is 600 r / min and the ball milling time is 24 h. After the ball milling is completed, the slurry is treated according to the same drying process as step 2, and then the dried powder is fully ground and passed through a 150-mesh sieve to obtain a uniform and fine powder; 0.25 g of the above powder is weighed and loaded into a cylindrical mold with a diameter of 10 mm, and then an electric tablet press is used to obtain a ceramic disc at a pressure of 1.5 MPa and a holding time of 1 min, and then a cold isostatic press is used to obtain a dense, crack-free unsintered sheet ceramic at a pressure of 300 MPa and a holding time of 1 min; Step 4: Place the above ceramic sheet in a muffle furnace for sintering treatment. The treatment process is to keep warm at 1145 °C for 2 hours. The sintering atmosphere is air. The heating rate of the muffle furnace during sintering is 5 °C / min. The cooling method is natural cooling with the furnace. The sintered dielectric ceramic sheet is polished with 1000 mesh and 2000 mesh sandpaper until it is smooth to obtain dielectric ceramics.

[0045] Example 5 A method for preparing a dielectric ceramic comprises the following steps: Step 1: According to 0.94Bi 0.475 Dy 0.025 Na 0.5 The chemical formula stoichiometric ratio of TiO3-0.06BaTiO3 is as follows: Bi2O3, Ba2CO3, Na2CO3, Dy2O3, SrCO3 and TiO2 with a purity higher than 99.5% from Aladdin Company are weighed as raw materials; Step 2: The weighed raw materials are placed in a nylon ball mill filled with zirconium oxide balls, anhydrous ethanol is added as a ball milling medium, and ball milling is performed once. The speed of the ball milling is 600 r / min, and the ball milling time is 24 h; the obtained slurry is placed in a petri dish and dried at 90 ° C for 12 h; the dried powder is placed in an alumina crucible and pre-sintered at 855 ° C for 4 h to obtain a ceramic powder precursor; Step 3: The ceramic powder precursor is crushed and ball-milled twice using anhydrous ethanol as a medium. The ball milling speed is 600 r / min and the ball milling time is 24 h. After the ball milling is completed, the slurry is treated according to the same drying process as step 2, and then the dried powder is fully ground and passed through a 100-mesh sieve to obtain a uniform and fine powder; 0.22 g of the above powder is weighed and loaded into a cylindrical mold with a diameter of 10 mm, and then an electric tablet press is used to obtain a ceramic disc at a pressure of 1.5 MPa and a holding time of 1 min, and then a cold isostatic press is used to obtain a dense, crack-free unsintered sheet ceramic at a pressure of 300 MPa and a holding time of 1 min; Step 4: Place the above ceramic sheet in a muffle furnace for sintering treatment. The treatment process is to keep warm at 1145 °C for 2 hours. The sintering atmosphere is air. The heating rate of the muffle furnace during sintering is 5 °C / min. The cooling method is natural cooling with the furnace. The sintered dielectric ceramic sheet is polished with 800 mesh and 1500 mesh sandpaper until it is smooth to obtain dielectric ceramics.

[0046] Example 6 A method for preparing a dielectric ceramic comprises the following steps: Step 1: According to 0.94Bi 0.475 Dy 0.025 Na 0.5 The chemical formula stoichiometric ratio of TiO3-0.06BaTiO3 is as follows: Bi2O3, Ba2CO3, Na2CO3, Dy2O3, SrCO3 and TiO2 with a purity higher than 99.5% from Aladdin Company are weighed as raw materials; Step 2: The weighed raw materials are placed in a nylon ball mill filled with zirconium oxide balls, anhydrous ethanol is added as a ball milling medium, and ball milling is performed once. The speed of the ball milling is 600 r / min, and the ball milling time is 24 h; the obtained slurry is placed in a petri dish and dried at 100 ° C for 12 h; the dried powder is placed in an alumina crucible and pre-sintered at 855 ° C for 4 h to obtain a ceramic powder precursor; Step 3: The ceramic powder precursor is crushed and ball-milled twice using anhydrous ethanol as a medium. The ball milling speed is 600 r / min and the ball milling time is 24 h. After the ball milling is completed, the slurry is treated according to the same drying process as step 2, and then the dried powder is fully ground and passed through a 200-mesh sieve to obtain a uniform and fine powder; 0.24 g of the above powder is weighed and loaded into a cylindrical mold with a diameter of 10 mm, and then an electric tablet press is used to obtain a ceramic disc at a pressure of 1.5 MPa and a holding time of 1 min, and then a cold isostatic press is used to obtain a dense, crack-free unsintered sheet ceramic at a pressure of 300 MPa and a holding time of 1 min; Step 4: Place the above ceramic sheet in a muffle furnace for sintering treatment. The treatment process is to keep warm at 1145 °C for 2 hours. The sintering atmosphere is air. The heating rate of the muffle furnace during sintering is 3 °C / min. The cooling method is natural cooling with the furnace. The sintered dielectric ceramic sheet is polished with 800 mesh and 2000 mesh sandpaper until it is smooth to obtain dielectric ceramics.

[0047] Example 7 A method for preparing a dielectric ceramic comprises the following steps: Step 1: According to 0.75Bi (703 / 1500) Dy (47 / 1500) Na 0.5 Stoichiometric ratio of TiO3-0.25SrTiO3 Bi2O3, Ba2CO3, Na2CO3, Dy2O3, SrCO3 and TiO2 with purity higher than 99.5% from Aladdin Company were weighed as raw materials; Step 2: The weighed raw materials are placed in a nylon ball mill filled with zirconium oxide balls, anhydrous ethanol is added as a ball milling medium, and ball milling is performed once. The speed of the ball milling is 600 r / min, and the ball milling time is 24 h; the obtained slurry is placed in a petri dish and dried at 110 ° C for 12 h; the dried powder is placed in an alumina crucible and pre-sintered at 855 ° C for 4 h to obtain a ceramic powder precursor; Step 3: The ceramic powder precursor is crushed and ball-milled twice using anhydrous ethanol as a medium. The ball milling speed is 600 r / min and the ball milling time is 24 h. After the ball milling is completed, the slurry is treated according to the same drying process as step 2, and then the dried powder is fully ground and passed through a 150-mesh sieve to obtain a uniform and fine powder; 0.25 g of the above powder is weighed and loaded into a cylindrical mold with a diameter of 10 mm, and then an electric tablet press is used to obtain a ceramic disc at a pressure of 1.5 MPa and a holding time of 1 min, and then a cold isostatic press is used to obtain a dense, crack-free unsintered sheet ceramic at a pressure of 300 MPa and a holding time of 1 min; Step 4: Place the above ceramic sheet in a muffle furnace for sintering treatment. The treatment process is to keep warm at 1145 °C for 2 hours. The sintering atmosphere is air. The heating rate of the muffle furnace during sintering is 3 °C / min. The cooling method is natural cooling with the furnace. The sintered dielectric ceramic sheet is polished with 600 mesh and 1200 mesh sandpaper until it is smooth to obtain dielectric ceramics.

[0048] Example 8 A method for preparing an energy storage-fluorescent dielectric capacitor with a transparent shell comprises the following steps: The dielectric ceramic prepared in Example 1 was placed in magnetron sputtering to prepare a transparent conductive electrode: First, clean the magnetron sputtering chamber and use a mechanical pump and a vacuum pump to pump the chamber to a vacuum degree of 4×10 -5 Pa or less; introduce mixed gas into the chamber at a volume ratio of argon: oxygen = 99.5:0.5, and adjust the valve to stabilize the pressure in the chamber at 1 Pa; Then, AZO (aluminum-doped zinc oxide) target was selected as the sputtering target, and the sputtering process was set to start sputtering the AZO transparent electrode. The specific process was: DC sputtering power 100 W, sample stage deposition temperature 25 °C, sputtering time 60 min, and electrode thickness of about 40 nm. Finally, after the sputtering is completed, the above mixed gas is quickly introduced to make the pressure in the chamber 2×10 4 Pa, set up an annealing process to heat treat the AZO electrode. The specific process is: the sample stage is heated to 600 °C at a heating rate of 10 °C / min and kept at this temperature for 1 h, and then cooled naturally to complete the electrode annealing treatment; Using a reflow soldering machine from Tongzhi Technology Co., Ltd., solder the tinned iron-aluminum alloy pins to the ceramic sheet on which the electrodes were prepared in step 5 at 260°C; PMMA (polymethyl methacrylate) was selected as the outermost shell packaging material of the dielectric ceramic capacitor. The ceramic sheet with prepared electrodes and pins was placed in a metal mold with a diameter of 12 mm and a thickness of 1 mm. The PMMA material was melted at about 210 ° C and injected into the mold. The curing time was 5 min. After cooling, the encapsulated capacitor was slightly polished and modified to obtain an energy storage-fluorescent dielectric capacitor with a transparent shell.

[0049] Example 9 Different from Example 8, the dielectric ceramic prepared in Example 2 is used in this example, and the rest of the preparation process and parameters are the same as those in Example 8, thereby obtaining an energy storage-fluorescent dielectric capacitor with a transparent shell.

[0050] Example 10 Different from Example 8, the dielectric ceramic prepared in Example 3 is used in this example, and the rest of the preparation process and parameters are the same as those in Example 8, thereby obtaining an energy storage-fluorescent dielectric capacitor with a transparent shell.

[0051] Embodiment 11 Different from Example 8, the dielectric ceramic prepared in Example 4 is used in this example, and the rest of the preparation process and parameters are the same as those in Example 8, thereby obtaining an energy storage-fluorescent dielectric capacitor with a transparent shell.

[0052] Example 12 A method for preparing an energy storage-fluorescent dielectric capacitor with a transparent shell comprises the following steps: The dielectric ceramic prepared in Example 5 was placed in magnetron sputtering to prepare a transparent conductive electrode: First, clean the magnetron sputtering chamber and use a mechanical pump and a vacuum pump to pump the chamber to a vacuum degree of 5×10 -5 Pa or less; introduce mixed gas into the chamber at a volume ratio of argon: oxygen = 99.5:0.5, and adjust the valve to stabilize the pressure in the chamber at 2 Pa; Then, ITO (indium tin oxide) target was selected as the sputtering target, and the sputtering process was set to start sputtering the ITO transparent electrode. The specific process was: DC sputtering power 90 W, sample stage deposition temperature 25 °C, sputtering time 30 min, and electrode thickness of about 30 nm. Finally, after the sputtering is completed, the above mixed gas is quickly introduced to make the pressure in the chamber 3×10 4 Pa, set up an annealing process to heat treat the ITO electrode. The specific process is: the sample stage is heated to 500 °C at a heating rate of 10 °C / min and kept at this temperature for 1 h, and then cooled naturally, thus completing the electrode annealing treatment; Using a reflow soldering machine from Tongzhi Technology Co., Ltd., solder the tinned iron-aluminum alloy pins to the ceramic sheet on which the electrodes were prepared in step 5 at 260°C; PC (polycarbonate) was selected as the outermost shell packaging material of the dielectric ceramic capacitor; the ceramic sheet with prepared electrodes and pins was placed in a metal mold with a diameter of 12 mm and a thickness of 1 mm, the PC material was melted at about 230 ℃ and injected into the mold, and the curing time was 8 min. After cooling, the packaged capacitor was slightly polished and modified to obtain an energy storage-fluorescent dielectric capacitor with a transparent shell.

[0053] Embodiment 13 A method for preparing an energy storage-fluorescent dielectric capacitor with a transparent shell comprises the following steps: The dielectric ceramic prepared in Example 6 was placed in magnetron sputtering to prepare a transparent conductive electrode: First, clean the magnetron sputtering chamber and use a mechanical pump and a vacuum pump to pump the chamber to a vacuum degree of 3×10 -5 Pa or less; introduce mixed gas into the chamber at a volume ratio of argon: oxygen = 99.5:0.5, and adjust the valve to stabilize the pressure in the chamber at 0.5 Pa; Then, ITO (indium tin oxide) target was selected as the sputtering target, and the sputtering process was set to start sputtering the ITO transparent electrode. The specific process was: DC sputtering power 95 W, sample stage deposition temperature 20 °C, sputtering time 40 min, and electrode thickness of about 35 nm. Finally, after the sputtering is completed, the above mixed gas is quickly introduced to make the pressure in the chamber 1×10 4Pa, set up an annealing process to heat treat the ITO electrode. The specific process is: the sample stage is heated to 550 °C at a heating rate of 10 °C / min and kept at this temperature for 1.5 h, and then cooled naturally, thus completing the electrode annealing treatment; Using a reflow soldering machine from Tongzhi Technology Co., Ltd., solder the tinned iron-aluminum alloy pins to the ceramic sheet on which the electrodes were prepared in step 5 at 260°C; PC (polycarbonate) was selected as the outermost shell packaging material of the dielectric ceramic capacitor. The ceramic sheet with prepared electrodes and pins was placed in a metal mold with a diameter of 12 mm and a thickness of 1 mm. The PC material was melted at about 225 ° C and injected into the mold. The curing time was 10 min. After cooling, the encapsulated capacitor was slightly polished and modified to obtain an energy storage-fluorescent dielectric capacitor with a transparent shell.

[0054] Embodiment 14 A method for preparing an energy storage-fluorescent dielectric capacitor with a transparent shell comprises the following steps: The dielectric ceramic prepared in Example 7 was placed in magnetron sputtering to prepare a transparent conductive electrode: First, clean the magnetron sputtering chamber and use a mechanical pump and a vacuum pump to pump the chamber to a vacuum degree of 2×10 -5 Pa or less; introduce mixed gas into the chamber at a volume ratio of argon: oxygen = 99.5:0.5, and adjust the valve to stabilize the pressure in the chamber at 1.5 Pa; Then, FTO (fluorine-doped tin oxide) target was selected as the sputtering target, and the sputtering process was set to start sputtering the FTO transparent electrode. The specific process was: DC sputtering power 100 W, sample stage deposition temperature 30 °C, sputtering time 30 min, and electrode thickness of about 40 nm. Finally, after the sputtering is completed, the above mixed gas is quickly introduced to make the pressure in the chamber 2×10 4 Pa, set up an annealing process to heat treat the FTO electrode. The specific process is: the sample stage is heated to 600 °C at a heating rate of 10 °C / min and kept at this temperature for 2 h, and then cooled naturally to complete the electrode annealing treatment; Using a reflow soldering machine from Tongzhi Technology Co., Ltd., solder the tinned iron-aluminum alloy pins to the ceramic sheet on which the electrodes were prepared in step 5 at 260°C; Epoxy resin E51 (Phoenix brand) was selected as the outermost shell packaging material of the dielectric ceramic capacitor. The ceramic sheet with prepared electrodes and pins was placed in a metal mold with a diameter of 12 mm and a thickness of 1 mm. The epoxy resin E51 material was melted at about 200 ° C and injected into the mold. The curing time was 5 min. After cooling, the encapsulated capacitor was slightly polished and modified to obtain an energy storage-fluorescent dielectric capacitor with a transparent shell.

[0055] Embodiment 15 A method for preparing a dielectric ceramic comprises the following steps: Step 1: According to 0.94Bi 0.475 Dy 0.025 Na 0.5 The chemical formula stoichiometric ratio of TiO3-0.06BaTiO3 is as follows: Bi2O3, Ba2CO3, Na2CO3, Dy2O3, SrCO3 and TiO2 with a purity higher than 99.5% from Aladdin Company are weighed as raw materials; Step 2: The weighed raw materials are placed in a nylon ball mill filled with zirconium oxide balls, anhydrous ethanol is added as a ball milling medium, and ball milling is performed once. The speed of the ball milling is 650 r / min, and the ball milling time is 32 h; the obtained slurry is placed in a petri dish and dried at 100 ° C for 24 h; the dried powder is placed in an alumina crucible and pre-sintered at 875 ° C for 3 h to obtain a ceramic powder precursor; Step 3: The ceramic powder precursor is crushed and ball-milled twice using anhydrous ethanol as a medium. The ball milling speed is 600 r / min and the ball milling time is 24 h. After the ball milling is completed, the slurry is treated according to the same drying process as step 2, and then the dried powder is fully ground and passed through a 150-mesh sieve to obtain a uniform and fine powder; 0.25 g of the above powder is weighed and loaded into a cylindrical mold with a diameter of 10 mm, and then an electric tablet press is used to obtain a ceramic disc at a pressure of 4 MPa and a holding time of 5 min, and then a cold isostatic press is used to obtain a dense, crack-free unsintered sheet ceramic at a pressure of 100 MPa and a holding time of 5 min; Step 4: Place the above ceramic sheet in a muffle furnace for sintering treatment. The treatment process is to keep warm at 1160 ° C for 4 hours. The sintering atmosphere is air. The heating rate of the muffle furnace during sintering is 5 ° C / min. The cooling method is natural cooling with the furnace. The sintered dielectric ceramic sheet is polished with 1000 mesh and 2000 mesh sandpaper until it is smooth to obtain dielectric ceramics.

[0056] Figure 1 This is a schematic diagram of the three-dimensional structure of an energy storage-fluorescence dielectric capacitor with a transparent shell prepared using the dielectric ceramics prepared in Examples 1 to 4. It can be seen that the transparent ceramic capacitor prepared by the present invention is mainly composed of a dielectric ceramic sheet, transparent conductive electrodes on both sides of the ceramic sheet, pins, and an outer encapsulated transparent polymer shell from the inside to the outside.

[0057] Figure 2The two-dimensional structural schematic diagram of the energy storage-fluorescence dielectric capacitor with a transparent shell prepared by using the dielectric ceramics prepared in Examples 1 to 4. It can be seen from the two-dimensional structural diagram that the transparent ceramic capacitor prepared by the present invention has the following structural characteristics: ① The transparent conductive electrodes cover the two sides of the ceramic sheet, but the electrode diameter of each side is smaller than the diameter of the ceramic sheet, thereby avoiding conduction between the upper and lower electrodes; ② The end position of the alloy pin is tightly combined with the electrode after soldering; ③ The transparent polymer shell of the outer layer package completely wraps the ceramic sheet and the electrode and partially wraps the pin, and finally the ceramic sheet, the electrode, and the pin are tightly fixed.

[0058] Figure 3 The X-ray diffraction patterns of the dielectric ceramics prepared in Examples 1 to 4 are as follows. It can be seen from the figure that the dielectric ceramics prepared in the present invention all have a standard perovskite structure without impurities. It can be seen that the components of the present invention are reasonable, the process control is accurate, and the target product is successfully synthesized.

[0059] Figure 4 The scanning electron microscope pictures of the dielectric ceramics prepared in Examples 1 to 4 show that the ceramics are relatively dense and have uniform grain sizes, so the prepared transparent ceramic capacitors may achieve a higher breakdown field resistance.

[0060] Figure 5 The excitation spectrum of the energy storage-fluorescence dielectric capacitor with a transparent shell prepared by using the dielectric ceramics prepared in Examples 1 to 4 can be seen that Dy 3+ The excitation spectrum peak of the ions has high intensity and clear peak shape, proving that the multifunctional energy storage-fluorescence ceramic capacitor has good fluorescence properties.

[0061] Figure 6 This is an emission spectrum diagram of an energy storage-fluorescence dielectric capacitor with a transparent shell prepared using the dielectric ceramics prepared in Examples 1 to 4. It can be seen that the emission spectrum in the figure shows obvious blue and yellow light emissions, and the spectrum peaks are sharp, and the yellow light is greater than the blue light. It can be seen that the energy storage-fluorescence ceramic capacitor has excellent white light characteristics.

[0062] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A dielectric ceramic, characterized in that: The chemical formula of the dielectric ceramic is nBi x Dy i Na 0.5 TiO3-(1-n)BaTiO3 or nBi x Dy i Na 0.5 TiO3-(1-n)SrTiO3; wherein: 0.75≤n≤0.94; 0.45≤x≤0.475; 0.025≤i≤0.

035.

2. A dielectric ceramic according to claim 1, characterized in that: The chemical formula of the dielectric ceramic is 0.94Bi 0.475 Dy 0.025 Na 0.5 TiO3-0.06BaTiO3, 0.75Bi (703 / 1500) Dy (47 / 1500) Na 0.5 TiO3-0.25BaTiO3, 0.94Bi 0.475 Dy 0.025 Na 0.5 TiO3-0.06SrTiO3 or 0.75Bi (703 / 1500) Dy (47 / 1500) Na 0.5 TiO3-0.25SrTiO3.

3. The method for preparing a dielectric ceramic according to claim 1 or 2, characterized in that: The following steps are involved: Weigh Bi2O3, Ba2CO3, Na2CO3, Dy2O3, SrCO3 and TiO2 as raw materials according to the stoichiometric ratio of claim 1 or 2; The raw materials are ball-milled once, and the obtained slurry is dried and pre-sintered in sequence to obtain a ceramic powder precursor; The ceramic powder precursor is subjected to secondary ball milling, tableting, cold isostatic pressing and sintering in sequence to obtain dielectric ceramics.

4. The method for preparing a dielectric ceramic according to claim 3, characterized in that: The purity of Bi2O3, Ba2CO3, Na2CO3, Dy2O3, SrCO3 and TiO2 is not less than 99.5%; The rotation speed of the first ball milling and the second ball milling is 600-650 r / min, the ball milling time is 20-32 h, and the ball milling medium is one of anhydrous ethanol or distilled water; The drying time is 12-24 h; the pre-burning temperature is 855-875°C and the time is 3-5 h.

5. The method for preparing a dielectric ceramic according to claim 3, characterized in that: The tableting pressure is 1.5-4 MPa, and the holding time is 1-5 min; The pressure during the cold isostatic pressing process is 100-300 MPa, and the holding time is 1-5 min.

6. The method for preparing a dielectric ceramic according to claim 3, characterized in that: The sintering process is carried out at a temperature of 1140-1160° C. and for a time of 2-4 h.

7. An energy storage-fluorescent dielectric capacitor with a transparent shell, characterized in that: The components of the energy storage-fluorescent dielectric capacitor with a transparent shell include the dielectric ceramic according to claim 1 or 2, a transparent conductive electrode, a pin and a transparent shell; The transparent conductive electrode is arranged on the surface of the dielectric ceramic; the pins are welded on both sides of the dielectric ceramic; and the transparent shell is encapsulated outside the dielectric ceramic, the transparent conductive electrode and the pins.

8. The method for preparing an energy storage-fluorescent dielectric capacitor with a transparent shell as claimed in claim 7, characterized in that: The following steps are involved: A transparent conductive electrode is sputtered on the surface of the dielectric ceramic, and then a lead is welded on both sides of the dielectric ceramic to obtain a component; A transparent shell is encapsulated on the outside of the component to obtain an energy storage-fluorescent dielectric capacitor with a transparent shell.

9. The method for preparing an energy storage-fluorescent dielectric capacitor with a transparent shell according to claim 8, characterized in that: The specific process of sputtering the transparent conductive electrode is: First, the vacuum degree in the deposition chamber was pumped down to 5×10 -5 Pa; then, a mixed gas of argon and oxygen in a volume ratio of 99.5:0.5 is introduced into the deposition chamber to keep the pressure in the deposition chamber stable at 0.5-2 Pa; Then, a transparent conductive electrode with a thickness of 20-40 nm was prepared according to the process parameters of DC sputtering power of 90-100 W, sample stage deposition temperature of 20-30 °C, and sputtering time of 30-60 min. Finally, after the above sputtering is completed, a mixed gas of argon and oxygen with a volume ratio of 99.5:0.5 is introduced to keep the pressure in the chamber stable at 1×10 4 - 3×10 4 Pa, and raising the temperature of the sample stage to 500-600 °C and keeping the temperature for 1-3 h to complete the annealing treatment of the electrode, thereby obtaining the transparent conductive electrode; The transparent conductive electrode is any one of ITO, AZO and FTO.

10. The method for preparing an energy storage-fluorescent dielectric capacitor with a transparent shell according to claim 8, characterized in that: The pin welding temperature is 260-300°C; the transparent shell is a polymer transparent shell; the packaging temperature of the polymer transparent shell is 200-250°C, and the curing time is 5-10 min; The pins are tin-plated iron-aluminum alloy pins; the polymer material is one or two of PMMA, PC and epoxy resin E51.

Citation Information

Patent Citations

  • A package for an electrical device

    CN102210037A

  • Manufacturing method for transparent capacitor

    CN103594333A

  • Full-transparent film voltage controlled varactor and preparation method thereof

    CN104134541A

  • Light enhancement effect transparent supercapacitor and preparation method thereof

    CN111540616A

  • Sodium bismuth titanate-based dielectric ceramic with energy storage and fluorescence characteristics and preparation method thereof

    CN117623765A